2001
DOI: 10.1046/j.1365-2850.2001.00384.x
|View full text |Cite
|
Sign up to set email alerts
|

The value of community mental health nurses based in primary care teams: ‘switching the light on in a cellar’

Abstract: This paper explores the impact of placing Community Mental Health Nurses (CMHNs) at two primary care practices in South Staffordshire. Data were collected by means of a questionnaire which was sent to primary care personnel at these practices, to ascertain their opinions with respect to the contribution of practice-based CMHNs. Overall, primary care personnel were satisfied with the quality of the service received from the CMHNs, especially in terms of improved communication. They felt that the new arrangement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 26 publications
(29 reference statements)
2
31
0
Order By: Relevance
“…Primary care settings are taking centre stage in the provision of services to people with mental health problems (Crawford et al . 2001).…”
Section: Organization and Operation Of New Psychiatric Units In Greecementioning
confidence: 99%
See 1 more Smart Citation
“…Primary care settings are taking centre stage in the provision of services to people with mental health problems (Crawford et al . 2001).…”
Section: Organization and Operation Of New Psychiatric Units In Greecementioning
confidence: 99%
“…MHNs have to understand and be trained in how to function in this context; how to engage with patients, families and other members of the primary care team and how to provide the various types of therapeutic interventions. As the MHN is considered the ‘cornerstone’ of the therapeutic team (Crawford et al . 2001), the administrative bodies responsible for monitoring the implementation of psychiatric reform in Greece should aim to attract and retain nursing staff in psychiatric health specialty.…”
Section: Introductionmentioning
confidence: 99%
“…Although some authors have identified CMHNs as able to make a significant contribution to improving client care (Crawford et al . 2001), others have noted that little attention has been paid to their selection and preparation (Hannigan 1997, Mead et al .…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is only possible if they are properly resourced as the increased presentation of transient mental health problems can result in CPNs having limited time for those with severe mental illness, who may present in lesser numbers but will have more complex needs. Primary care teams appear to welcome input from CPNs and there have been a number of studies that demonstrate this (Corney 1999, Crawford et al . 2001).…”
Section: Community Psychiatric Nurses (Cpns)mentioning
confidence: 99%